(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Since pollen and nectar are the primary food sources for bees, beekeeping is typically carried out in Kediri during the flowering season. However, the reliance on the flowering season makes beekeepers’ income insignificant and unstable. The Community Service Program (PKM) aims to assist partner organizations in enhancing research and development to produce bee forage plant varieties that bloom continuously and exhibit greater resistance to pests and diseases. The program also offers training on modern and efficient beekeeping techniques and pest and disease management and assists beekeepers in gaining market access and increasing the value of honey products. The program’s focus on increasing the value of honey products creates optimism about the economic growth potential, while promoting forest conservation and environmental sustainability. Additionally, the program provides financial assistance and supporting infrastructure for beekeepers. The implementation of this Community Service Program (PKM) introduces innovative solutions through partnerships between beekeepers and honey processing factories. In this collaboration, honey factories supply supplementary feed for the bees, allowing year-round beekeeping without dependence on the flowering season. As a result, the productivity of the beekeepers has increased, and their income has become more stable and significant each month. This innovation not only improves the welfare of the beekeepers but also creates a sustainable beekeeping model that supports the development of the honey industry in Kediri.